»Af alle mine lærere har Schmitt været den vigtigste«. Reinhart Kosellecks intellektuelle og personlige relationer til Carl Schmitt - Olsen, Niklas (Historisk Tidsskrift, 2013)
»Of all my teachers Schmitt was the most important« Reinhart Koselleck's intellectual and personal relations with Carl Schmitt The prominent historian of ideas and theoretician of history, Reinhart Koselleck, now eighty, for many years exerted a pronounced influence on German historical research. His name is inextricably linked with the monumental reference work Geschichtliche Grundbegriffe, where he has formulated a number of hypotheses on how the transition to the modern world can be discerned in changes in the use and significance of basic social and political concepts during the "Sattelzeit" (1750-1840). Internationally Koselleck's history of ideas has had a great impact. The same can be said of his numerous essays on historical theory and method, most of which were written from the beginning of the seventies till the beginning of the nineties. His influence is largely due to his constant ability to spawn innovative approaches to universal as well as specific themes dealing primarily with the rise of modernity and the conditions for man's historical consciousness. These topics are the grand leitmotiv of his scholarship.Koselleck's scholarly works can only be understood in the light of the powerful theoretical, methodological, thematic, stylistic, and even political inspiration exerted on him by the German legal scholar and political theoretician Carl Schmitt (1888-1985), who as a consequence of his intellectual support of National Socialism was academically and politically shunned after 1945. Koselleck's writings pay recognition to Schmitt in various ways, including references to and direct use of his ideas and concepts. Moreover, Koselleck in interviews has described his momentous meeting with Schmitt as well as a number of incidents relating to their intellectual and personal relationships, which developed through a long period of inspiration and counsel. There is much to indicate that the encounter with Schmitt and his works at the beginning of the fifties confirmed fundamental views that Koselleck had already derived from his war experiences. Koselleck's scientific and epistemological interests were deeply influenced by what he went through on the Eastern Front, in a Russian prisoner camp, and on clearing-up duties at Auschwitz, subsequent to his volunteering for duty in the German army in 1941. His writings must be read as a reaction to these experiences. His works evidence repeated attempts to grasp the historical background of the modern world, in particular the Second World War: how it was lived through, how it could be understood and coped with. It is also against the background of his war experience that one must understand Koselleck's pessimism regarding modern society, its politics, and science: he is suspicious of all pronouncements about societal progress, deeply sceptical of political democracy, and strongly in doubt whether mankind can learn from or understand history. Inspiration to make sense of the war was exactly what Koselleck found in Schmitt. Today he uses Schmitt differently than he did in the fifties, because his epistemological focus in relation to the war has changed. At the beginning of his career Koselleck, when he was trying to explain the causes of the war, was profoundly inspired by Schmitt's scientific methods and theories - and by his antidemocratic views as well. But from the beginning of the seventies, as he turned to the conditions of understanding the war experience, he began to tone down and modify his use of Schmitt. In the course of that process Schmitt's political inspiration gradually lost its hold. This is particularly true of his critique of liberalism, which was one of the elements Koselleck had found most alluring in his first encounter with Schmitt towards the end of the forties. Koselleck's scholarly production and his attitude towards Schmitt in the context described here can be roughly divided into four phases: from ca. 1953 to 1959, from ca. 1960 to 1970, from ca. 1970 to 1990, and finally, from ca. 1990 to 2000. Available sources do not permit an exact delimitation of these phases, nor do they afford an exhaustive explanation of what motivated his development or where to set the decisive turning-point. On the other hand, by analysing reactions to Koselleck's relation to Schmitt it is possible to throw new light on central ideological and intellectual positions in recent German social science and history. From the fifties to the seventies Koselleck's close intellectual and political affinities with Schmitt cast him academically and politically in an unfavourable light. More recently, as Koselleck has dampened his evaluation of Schmitt and, indeed, increasingly confronted his political views, the negative assessment of Koselleck has apparently receded. What direction Koselleck's historical thinking has taken within the last few years will soon be seen, when before long he publishes two new essay collections. These volumes will presumably show how extensively he has further downplayed his enthusiasm for Schmitt's professional views and broken with the political identification. But there is one thing we may hardly expect, and that is personal dissociation. Koselleck has often expressed his enormous respect for Schmitt, and in assessing Schmitt's significance for his own scholarly production, he has recently stated: "Of all my teachers - Gadamer, Conze, Lövith, Kuhn, Heidegger - Schmitt was the most important." Translated by Michael Wolfe